Chloroquine Induced Retinal Toxicity- A Case Report - Nahar, Nazmun; Barua, Palash; Shahnaz, Kaniz Ahmed (Journal of National Institute of Ophthalmology, 2022)
Chloroquine (CQ) and hydroxychloroquine (HCQ) is used increasingly in the management of variety of autoimmune disorders with well-established role in dermatology, rheumatology, and oncology. Retinopathy in the form of maculopathy occurs due to long term use of CQ or HCQ in large dose, have been associated with irreversible visual loss. A middle aged diabetic patient had been complaining of profound dimness of vision following uncomplicated cataract surgery on both eyes. She had a very good vision (6/6) in both eyes which reduced to 6/60 and 5/60 in right and left eye respectively. Colour fundus photography (CFP), Visual field analysis (VFA), Optical coherence tomography (OCT) and Fundus fluorescein angiography (FFA) revealed the changes consistent with “bulls’ eye maculopathy”. Treatment was unsatisfactory with antioxidant and neuro vitamin. J. Natl. Inst. Ophthalmol. 2022; 5(2):42-44